Authentic learning in senior secondary music pedagogy: an examination of teaching practice in high-achieving school music programmes. Issue 2 (17th July 2021) - White, Rachel
Abstract: Authentic learning approaches are designed to immerse students in contexts that promote real-life applications of knowledge, and provide meaningful learning experiences beyond the abstract instruction of the classroom. In a grounded theory study of music teaching practice in high-achieving schools, 50 teachers from 23 schools across New South Wales (NSW), Australia, were asked to describe how they taught their senior secondary students and the musical environment they curated within their school. Through examination of the interview data, authentic learning exposed itself as uniquely situated in classroom music teaching of high-achieving music programmes for senior secondary students in NSW. This is shown through the use of thorough inquiry-based and student-centred learning tasks like video journals, the use of professional resources and expertise and collaborative learning in authentic contexts, in and outside of the classroom.